Nutritional status of the elderly adult in Peru, 2005-2013 - Pajuelo Ramírez, Jaime (2022)
Introduction. 13% of the general population is older than 60 years. Objective. To determine the nutritional status of the elderly and its evolution over time (2005-2013). Methods. Study based on secondary sources: ENIN 2005 and ENAHO 2012-2013. The diagnosis was made by estimating the body mass index < 23 deficit, 23 to 26.9 normal, 27 to 31.9 overweight and ≥ 32 kg/m2 obesity. Women with waist circumference ≥ 88 cm and men ≥ 102 cm were considered high cardiovascular risk. Results. In ENIN the deficit was 30.4 %, overweight 17.5 % and obesity 8.7 %, while in ENAHO 28.8 %, 18,9 % and 9.5%, respectively. The deficit affected more men (33.1 % vs 29.1 %). Their prevalence increased as age and altitude level increased. Overweight was more frequent in women (21.4 % vs 20.2 %) as well as obesity (13.5 % vs 13.3 %), in both the behavior with age and altitude levels were similar since their prevalence decreased. Women had a higher cardiovascular risk than men and in both their prevalence decreased as age and altitude increased. Conclusion. The biggest problem presented by the elderly, in the period 2005-2013, was the deficit, being the males, those over 80 years old and those who lived above 3000 meters above sea level the most affected. Abdominal obesity was more present in women, being the most affected the group of 60 to 69 years old and those who lived below 1000 meters above sea level.